Uma técnica de inspeção para documentos de especificação de requisitos para sistemas multiagentes - Mendonça, Giovane D’Avila (2021)
Multiagent systems are characterized by being composed of several agents interacting with each other. An agent is a process capable of performing actions without user intervention, moreover, an agent has the hability to perceive and respond to changes in the environment. However, the development of this kind of system brought new challenges to the software engineering. Among them, the need to adapt the requirements engineering to the context of multi-agent systems. Requirements Engineering is an important area of Software Engineering that is concerned with eliciting, analyzing, specifying, and validating software requirements to ensure the correct understanding of what needs to be developed. The objective of requirements specification is to provide a detailed description of what the system must do. It involves the production of a document that can be systematically reviewed, evaluated, and approved. Problems in the requirements specification are pointed out as the main causes of failures in software projects, in this sense, requirements verification aims to ensure the quality of the software being developed. Thus, several inspection techniques were proposed for requirements verification. Within the context of inspections is the technique of Perspective-Based Reading (PBR) which has been shown to be effective in detecting failures in software requirements. In this way, we believe that requirements engineering for multiagent systems can benefit from the application of this technique, in order to improve and ensure the requirements specification quality. However, Perspective-Based Reading does not allow inspecting specific features of multiagent systems. Thus, this research has as its objective to adapt this inspection technique in order to verify requirements specification documents for multiagent systems. We have also produced a template for requirements specification document that supports the Belief-Desire-Intention model. For this, we extended the ISO/IEC/IEEE 29148:2018 standard, considering that, selecting a documentation standard is an important step for describing requirements specifications. Our adaptation of the PBR technique was specifically developed for this requirements representation template, nevertheless we believe it can be applied to other requirement specification documents with little modifications. It is important to highlight that this inspection technique and the template standard extension are being proposed to be used in a specific requirements engineering process for multiagent systems currently under development. Key-words: Requirements Engineering. Requirements Specification. Requirements Validation. Multi-agent Systems. BDI Model. Standard ISO/IEC/IEEE 29148:2018.